Analisis Perhitungan Poros Roda Depan Pada Sepeda Motor Honda Beat Street 2016 - Mohamad Nadjib Maulana; Jojo Sumarjo; Aripin Aripin (Peneliti.net, 2022)
In two-wheeled vehicles there are many very important components, one of which is the axle shaft. The axle that will be discussed is the axle on the front whell of the Honda Beat Street 2016. This study aims to determine the axle planning that is safe to use. The materials used to design the shaft are carbon steel for machine construction and cold-finished bar steel for the shaft with the symbol S45C-D with a tensile strength of 60 kg/mm2. The result of the calculation of the design of the shaft indicate that the design power is 9kW, the design torsional moment is 1278.37 kg·mm, the allowable stress is obtained by a value of 6.7 kg/mm2, from the calculation results it can be seen that the shear stress that occurs is smaller than the allowable stress, so it can be concluded that the planned shaft size is quite safe.